PENGARUH PEMBERIAN PUDING LABU KUNING (CUCURBITA MOSCHATA DURCH) TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI - Yohandrey, Febry; Kasmiyetti, Kasmiyetti; Handayani, Marni; Dwiyanti, Defriani; Edmon, Edmon (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2023)
ABSTRACTBackground: Hypertension as the Silent Killer because it is a deadly disease without any symptoms as a warning sign to its victims. Bukittinggi is ranked 4th with the highest hypertension prevalence rate in West Sumatra at 31.2% in 2018. Tigo Baleh Health Center is ranked as the first with the highest hypertension in Bukittinggi City. Non-pharmacological therapy management can be carried out in patients with hypertension sourced from local functional foods. Pumpkin is one of the local functional foods that has anti-hypertensive substances.Objectives: Hypertension is often referred to as the Silent Killer because it is a deadly disease without any symptoms as a warning sign to its victims. Bukittinggi is ranked 4th with the highest hypertension prevalence rate in West Sumatra at 31.2% in 2018. Tigo Baleh Health Center is ranked as the first with the highest hypertension in Bukittinggi City. Non-pharmacological therapy management can be carried out in patients with hypertension sourced from local functional foods. Pumpkin is one of the local functional foods that has anti-hypertensive substances. The purpose of this study was to determine the effect of giving pumpkin pudding on lowering blood pressure in patients with hypertension.Methods: This study used a Quasi Experiment Two Group Pretest-Postest design in the Tigo Baleh Health Center work area. The sampling technique was purposive sampling. Respondents in this study were 40 people who included the Treatment Group and the Control Group. Data analysis consisted of univariate analysis and bivariate analysis with the Dependent T-test to see the average differences of each experimental group also the Independent T-test to see the effect of changes in blood pressure after intervention from both experimental groups.Results The results showed an average blood pressure reduction of 20.35/8.05 mmHg in the treatment group and 3.30/4.35 mmHg in the control group. Also, there is a significant difference in mean blood pressure (p < 0.05) and there is a significant effect of blood pressure changes (p < 0.05) from both groups before and after hypertension.Conclusion: Pumpkin pudding is more effective in reducing blood pressure in patients with hypertension than pudding. Thus, it is recommended for the community to consume pumpkin pudding as a complementary therapy for lowering blood pressure.Keywords : Hypertension; Blood Pressure; Pumpkin Pudding ABSTRAKLatar belakang: Hipertensi termasuk penyakit yang mematikan tanpa disertai gejala yang terlebih dahulu sebagai tanda peringatan kepada korbannya. Bukittinggi termasuk urutan ke- 4 dengan angka prevalensi hipertensi tertinggi di Sumatera Barat yaitu 31,2% pada tahun 2018. Puskesmas Tigo Baleh menduduki peringkat pertama penderita hipertensi tertinggi di Kota Bukittinggi. Penatalaksanaan Terapi Non Farmakologi dapat dilakukan pada penderita hipertensi yang bersumber dari pangan fungsional lokal. Labu kuning merupakan salah satu pangan fungsional lokal yang memiliki zat anti hipertensi. Tujuan: Tujuan penelitian ini untuk mengetahui pengaruh pemberian puding labu kuning terhadap penurunan tekanan darah pada penderita hipertensi.Metode: Penelitian ini menggunakan desain Quasi Eksperimen Two Group Pretes-Postest di wilayah kerja Puskesmas Tigo Baleh. Teknik pengambilan sampel berupa Purposive Sampling. Responden dalam penelitian ini sebanyak 40 orang yang mencakup Kelompok Perlakuan dan Kelompok Kontrol. Analisis data terdiri dari analisis univariat dan analisis bivariat dengan uji T-test Dependent untuk melihat perbedaan rata – rata dalam masing – masing kelompok perlakuan dan kontrol serta uji T-test Indenpendent untuk melihat pengaruh perubahan tekanan darah setelah intervensi antara kelompok perlakuan dan kontrol.Hasil: Hasil penelitian menunjukkan rata- rata penurunan tekanan darah 20,35/8,05 mmHg pada kelompok perlakuan dan 3,30/4,35 mmHg pada kelompok kontrol. Serta, terdapat perbedaan rata-rata tekanan darah yang signifikan (p < 0,05) dan terdapat pengaruh perubahan tekanan darah yang signifikan (p < 0,05) dari kedua kelompok sebelum dan setelah intervensi. Simpulan: Puding labu kuning lebih efektif menurunkan tekanan darah pada penderita hipertensi dibandingkan puding. Sehingga, disarankan kepada masyarakat untuk mengonsumsi puding labu kuning sebagai terapi komplementer untuk penurunan tekanan darah.Kata Kunci : Hipertensi; Tekanan Darah; Puding Labu Kuning